2005
DOI: 10.1007/s10038-005-0323-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD14 promoter polymorphisms and soluble CD14 levels in mite allergen sensitization of children in Taiwan

Abstract: CD14 is responsible for environmental lipopolysaccharide recognition and is a positional candidate gene for allergy. We hypothesized that genetic polymorphisms in the promoter region of the CD14 gene may be associated with Dermatophagoides pteronysinnus (Der p) allergen sensitization in children. Three single nucleotide polymorphisms (SNPs) of the CD14 promoter region, C(À159)T, A(À1,145)G, and G(À1,359)T were genotyped, and analyzed in 240 randomized casecontrol school-age children in Taiwan. Serum concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
5
27
0
Order By: Relevance
“…Lower serum sCD14 levels in atopic adolescents found in our study corroborate reports from Sweden and Taiwan, which showed that atopic children had significantly lower serum sCD14 than non-atopic children (6,11). In contrast, other studies reported higher serum sCD14 levels in allergic alveolitis (12), atopic dermatitis (13), and asthma (14,15,20).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Lower serum sCD14 levels in atopic adolescents found in our study corroborate reports from Sweden and Taiwan, which showed that atopic children had significantly lower serum sCD14 than non-atopic children (6,11). In contrast, other studies reported higher serum sCD14 levels in allergic alveolitis (12), atopic dermatitis (13), and asthma (14,15,20).…”
Section: Discussionsupporting
confidence: 91%
“…The level of specific IgE in serum is a good marker of sensitisation but not of clinically symptomatic allergy, and new markers of atopic diseases have been investigated (3). One such potential marker is the cluster of differentiation 14 (CD14), a multifunctional receptor on the macrophages, monocytes, and dendritic cells that binds lipopolysaccharides (LPS) and other bacterial wall compounds, fungal wall components (β-glucan, mannans), and indoor allergens (dust mite and cockroach allergens) (4)(5)(6)(7). In serum it takes soluble form (sCD14), and its concentrations have been associated with serum IgE and asthma (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of previous studies indicate that the CD14 gene plays an important role in the determination of sensitisation to environmental allergens as well as in innate immunity against pathogens (Tan et al 2006). The results of association studies of the CD14 gene with atopic phenotype in our populations confirm the importance of not only promoter, but also exon polymorphisms in the CD14 gene in modulating expression and severity of the atopic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…at positions -1,619, -1,359, -1,145, -809, and -550) were characterised in the promoter of the gene encoding CD14. Vercelli et al (2001b) and Tan et al (2006) showed that carriers of the -1359T/-1145A/ -159C haplotype had the highest levels of IgE, and the lowest levels of sCD14, and conversely carriers of the 1359G/-1145G/-159T haplotype had the highest levels of sCD14 and the lowest IgE values. According to Martin et al (2006), during acute asthma, plasma sCD14 levels were higher, but increases were only in subjects with CD14 -159TT and -159CT, and not in those with -159CC.…”
Section: Introductionmentioning
confidence: 97%